Phát biểu của Chủ tịch Quốc hội Vương Đình Huệ khai mạc Kỳ họp thứ 4, Quốc hội khóa XV - Vương Đình Huệ (2022)
Toàn văn Phát biểu của Chủ tịch Quốc hội Vương Đình Huệ khai mạc Kỳ họp thứ 4, Quốc hội khóa XV